2013
DOI: 10.1166/msr.2013.1021
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry of CD38 in Different Cell Types in the Hypothalamus and Pituitary of Male Mice

Abstract: Oxytocin (OT) and arginine vasopressin (AVP) are neurohypophysial hormones. CD38 and cyclic ADP-ribose (cADPR) formation have been identified in the hypothalamus and are critical for OT, but not AVP, secretion, with profound consequential changes in social behaviors in mice. In the present study, we examined the immunolocalization of CD38, OT and AVP in different cell types in the hypothalamus and pituitary lobe of male mice. In the hypothalamus, CD38 immunoreactivity was found more commonly in OT neurons than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…While we could not detect CD38 expression in microglia in the postnatal periods examined here, this is not surprising. CD38 is known to be induced in response to microglial activation in pathological conditions, such as brain inflammation, which may not be the case in the developing brain (Akimoto et al, ; Ma et al, ; Mayo et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we could not detect CD38 expression in microglia in the postnatal periods examined here, this is not surprising. CD38 is known to be induced in response to microglial activation in pathological conditions, such as brain inflammation, which may not be the case in the developing brain (Akimoto et al, ; Ma et al, ; Mayo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the brain, CD38 expression has been observed not only in oxytocin neurons but also in glial cells, including astrocytes and microglia (Akimoto et al, ; Kou et al, ; Yamada, Mizuguchi, Otsuka, Ikeda, & Takahashi ). Ultrastructural analysis using adult rat brain demonstrated that CD38 immunoreactivity was found in a subset of pyramidal neurons and astrocytes, but not in microglia or oligodendrocytes (OLs) in the physiological condition (Yamada et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the sections were washed with PBS containing 0.3% TritonX-100 and coverslipped with anti-fade (Akimoto et al, 2013). Imaging was performed using an Olympus IX71 microscope.…”
Section: Methodsmentioning
confidence: 99%
“…In conclusion, it is clear that CD38 plays pivotal roles under neuronal physiological as well as pathophysiological conditions (Malavasi et al, 2008;Rah et al, 2012;Higashida, et al, 2012aAkimoto et al, 2013). DNA manipulation of CD38 and cADPR in the mAChR-signal cascade in NG108-15 cells revealed that CD38 has great impact on M-current inhibition.…”
Section: Discussionmentioning
confidence: 86%